PRAGMATIC EQUIVALENCE IN TRANSLATING CULTURE-BOUND SYMBOLS: THE CASE OF “XUMO QUSHI” IN ODIL YOQUBOV’S “ULUG‘BEK XAZINASI” - Abdullajon Ruziev (International Journal of Literature and Language Studies, 2026)
This article examines the pragmatic translation strategies applied to the culture-bound Uzbek expression “xumo qushi” across its four occurrences in the first part of Odil Yoqubov’s historical novel “Ulug‘bek Xazinasi” and its English translation The Treasure of Ulugbek. In Uzbek literary and cultural tradition, the xumo bird is a mythical symbol of divine fortune, royal destiny, and sacred authority, yet it has no established equivalent in English. Drawing primarily on Mona Baker’s theory of pragmatic and contextual equivalence and Eugene Nida’s concept of dynamic equivalence, the article argues that the translator’s decision to render the symbol differently in each narrative context reflects a principled pragmatic strategy rather than lexical inconsistency. The analysis demonstrates that translation of culture-specific mythological imagery requires sensitivity to communicative function, narrative register, and reader reception rather than formal correspondence to the source expression.